2021
DOI: 10.1186/s12951-021-01070-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitter-stimulated neuron-derived sEVs have opposite effects on amyloid β-induced neuronal damage

Abstract: The ratio of excitatory to inhibitory neurotransmitters is essential for maintaining the firing patterns of neural networks, and is strictly regulated within individual neurons and brain regions. Excitatory to inhibitory (E/I) imbalance has been shown to participate in the progression of neurodegenerative diseases, including Alzheimer's disease (AD). Glutamate excitotoxicity and GABAergic neuron dysfunction appear to be key components of the neuronal cell death that takes place in AD. Since extracellular vesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Extracellular vesicles (EVS) are the main carrier of intercellular information transmission. It is found that EVs of neurons are regulated by the balance of neurotransmitter level, and sev released by GABA treated neurons reduces Aβ Induced injury, while the SEV released by neurons treated with glutamate aggravated Aβ Toxicity reported by Dou et al [72]. The changes of glutamatergic, GABAergic and cholinergic will affect the dysfunction of neural activity, the distribution of amyloid and tau, and then induce AD, among which GABAergic has the greatest impact on cognitive ability recently reported by khan et al [73].…”
Section: Regulation Of Neurotransmitter Levelsmentioning
confidence: 85%
“…Extracellular vesicles (EVS) are the main carrier of intercellular information transmission. It is found that EVs of neurons are regulated by the balance of neurotransmitter level, and sev released by GABA treated neurons reduces Aβ Induced injury, while the SEV released by neurons treated with glutamate aggravated Aβ Toxicity reported by Dou et al [72]. The changes of glutamatergic, GABAergic and cholinergic will affect the dysfunction of neural activity, the distribution of amyloid and tau, and then induce AD, among which GABAergic has the greatest impact on cognitive ability recently reported by khan et al [73].…”
Section: Regulation Of Neurotransmitter Levelsmentioning
confidence: 85%
“…Opposite effects upon Aβ toxicity were observed since EVs from GABA‐treated neurons alleviate the damage caused by Aβ treatments in vitro (by increasing cells viability and decreasing apoptosis) and in vivo (due to improvements in spatial learning and memory abilities), while EVs derived from glutamate‐treated neurons aggravated the damage. These results indicate that the manipulation of EVs with different neurotransmitters may be interesting to unravelling AD pathogenesis pathways (Dou et al, 2021).…”
Section: Evs In the Study Of Ad And Pd Molecular Basismentioning
confidence: 91%
“…Regarding the isolation methods, UC is by far the most used in EVs with exosome‐like characteristics secreted from cellular models (Asai et al, 2015; Bai et al, 2021; Beretta et al, 2020; Bodart‐Santos et al, 2019; Candelario et al, 2020; Chen et al, 2020; Delenclos et al, 2017; Ding et al, 2022; Dou et al, 2021; Eitan et al, 2016; Emmanouilidou et al, 2010; Grey et al, 2015; Gustafsson et al, 2018; Harischandra et al, 2018; Harischandra et al, 2019; Imanbekova et al, 2021; Izadpanah et al, 2020; Koinuma et al, 2021; Lauritzen et al, 2019; Li et al, 2020; Li, Li, et al, 2022; Marzano et al, 2019; Meng et al, 2020; Micci et al, 2019; Nikitidou et al, 2017; Park et al, 2020; Santa‐Maria et al, 2012; Tang et al, 2022; Vrancx et al, 2021; Wang et al, 2012; Wei et al, 2020; Willén et al, 2017; Yang et al, 2020; Yuyama et al, 2019; Zarrin et al, 2021; Zhang, Xu, et al, 2020), whereas dgUC was employed in EVs isolation derived from brain tissue in nearly all studies presented (Asai et al, 2015; Cheng et al, 2020; Clayton et al, 2021; Cohn et al, 2021; Ding et al, 2022; Hurwitz et al, 2018a; Karampetsou et al, 2020; Lauritzen et al, 2019; Muraoka et al, 2021; Pérez‐González et al, 2012; Pérez‐González et al, 2020; Polanco et al, 2016; Polanco et al, 2021; Ruan et al, 2021; You et al, 2022; Yuyama et al, 2019).…”
Section: Methodologies Employed In Evs Isolation From Ad and Pd Mimic...mentioning
confidence: 99%
See 1 more Smart Citation
“…In neurological diseases, EVs have been reported to participate in neural repair in a variety of ways [ 15 ]. For example, the function of neuron-derived small EVs might be regulated by the status of neurotransmitter balance and that EVs might affect amyloid βtoxicity on neurons [ 16 ]. The unique advantage of EVs over existing delivery systems is their natural origin, which allows them to avoid phagocytosis, prolong the half-life of therapeutic agents, and reduce immunogenicity [ 17 ].…”
Section: Introductionmentioning
confidence: 99%